In vitro culture of hFOB1.19 osteoblast cells on TGF-β1-SF-CS three-dimensional scaffolds - TONG, SHUANG (Mol Med Rep, 2016)
The aim of the present study was to examine the biocompatibility of transforming growth factor-β1-silk fibroin-chitosan (TGF-β1-SF-CS) scaffolds. In order to provide an ideal scaffold for use in bone tissue engineering, TGF-β1 was introduced into the SF-CS scaffold in order to reconstruct a three dimensional scaffold, following which hFOB1.19 osteoblast cells were seeded onto TGF-β1-SF-CS and SF-CS scaffolds. On the TGF-β1-SF-CS and SF-CS scaffolds, the cell adhesion rate increased in a time-dependent manner. Scanning electron microscopy revealed that the cells grew actively and exhibited normal morphological features with multiple fissions, and granular and filamentous substrates were observed surrounding the cells. In addition, the cell microfilaments were closely connected with the scaffolds. The cells exhibited attached growth on the surfaces of the scaffolds, however, the growth also extended into the scaffolds. Cell Counting Kit-8 and ALP analyses revealed that TGF-β1 significantly promoted the growth and proliferation of the hFOB1.19 osteoblast cells in the SF-CS scaffolds, and the enhancement of osteoblast cell proliferation and activity by TGF-β1 occurred in a time-dependent manner. The TGF-β1-SF-CS composite material may offer potential as an ideal scaffold material for bone tissue engineering.